A new species of Terminalichus (Trombidiformes: Tenuipalpidae) from Thailand, with a key to the known species - Castro, Elizeu B. [UNESP]; Ochoa, Ronald; Feres, Reinaldo J.F. [UNESP] (Systematic and Applied Acarology Society, 2017)
A new species, Terminalichus simplex sp. nov., is described based on adult females, deutonymphs and protonymphs, collected on Terminalia catappa L. (Combretaceae) from Thailand. The relationship of Terminalichus with other brevipalpine genera is discussed and a key to species of Terminalichus, Tenuilichus, Amblypalpus, Colopalpus and Priscapalpus is provided.
Keywords: Brevipalpine; Combretaceae; False spider mite; Flat mite; Taxonomy; Terminalia catappa; Terminalichus simplex